Rate of Freeze Impacts the Survival and Immune Responses Post Cryoablation of Melanoma - Yakkala, Chakradhar; Dagher, Julien; Sempoux, Christine; Chiang, Cheryl Lai-Lai; Denys, Alban; Kandalaft, Lana E.; Koppolu, Bhanu; Duran, Rafael (Frontiers in Immunology, 2021)
The emergence of ablative therapies has revolutionized the treatment of inoperable solid tumors. Cryoablation stands out for its uniqueness of operation based on hypothermia, and for its ability to unleash the native tumor antigens, resulting in the generation of anti-tumor immune responses. It is not clearly understood how alterations in the rate of freeze impact the immune response outcomes. In this study, we tested fast freeze and slow freeze rates for their effectiveness and ability to elicit immune responses in a B16F10 mouse model of melanoma. Tumor bearing mice treated with fast freeze protocol survived better than the ones treated with slow freeze protocol. Fast freeze resulted in a higher magnitude of CD4+ and CD8+ T-cell responses, and a superior protection against tumor re-challenge as compared to slow freeze method. Thus, fast freeze rate should be applied in any future studies employing cryoablation as an in vivo vaccination tool in conjunction with targeted immunotherapies.